Teaching critical thinking with artificial intelligence: An information literacy training model at the FKKMK Library of Gadjah Mada University - Mohammad Riqzazulmi; Fitri Mutia; Sukirno; Tachiyya Naial Khusna (Daluang: Journal of Library and Information Science, 2026)
Purpose. This study investigates the incorporation of artificial intelligence (AI) into information literacy training in university libraries, with a focus on how AI may foster critical thinking and ethical awareness among students and staff. Methodology. The research employed a qualitative descriptive approach with data collected through interviews, observations, and documentation at the FKKMK Library of Gadjah Mada University. Thematic analysis was used to identify patterns in participants’ experiences and the role of librarians as facilitators. Results and discussion. The training model consisted of three main components: introducing AI concepts and ethical considerations, practising the use of generative AI tools for literature searching, summarisation, and academic writing, and critically evaluating AI outputs. The training enhanced participants’ ability to locate relevant sources, generate summaries, and support administrative tasks. It also highlighted challenges, such as difficulties in formulating effective prompts and the need for librarians to upgrade their AI competencies continuously. The findings show that AI-based literacy training not only improves technical proficiency but also nurtures reflective and critical engagement with digital tools. Conclusions. The study concludes that AI-driven information literacy programs in academic libraries can serve as an innovative model for strengthening users’ critical thinking, ethical responsibility, and digital literacy. Sustained librarian capacity-building and continuous training are essential to maximise the long-term benefits of AI integration in academic information services.